Notes on two species of the cavernicolous subgenus Neobisium (Blothrus) Schiödte, 1847 (Arachnida: Pseudoscorpiones) from Transylvania (Romania), with a key to the species of the Carpathian Mountains - Novák, János (Zootaxa, 2014)
Redescriptions of Neobisium (Blothrus) minutum (Tömösváry, 1882) and N. (B.) brevipes (Frivaldszky, 1865) are given, accompanied by new illustrations. Neobisium (B.) brevipes montanum is elevated to full species rank as N. (B.) montanum Beier, 1939. New records of N. (B.) minutum and N. (B.) brevipes from Romania are presented. A key to the members of the subgenus Blothrus occurring in the Carpathian Mountains is provided.